Lithium-free positive electrode FeF3 active material as well as preparation method and application thereof
Through the gas-solid reaction method of directly reacting F2 with iron precursor, the anhydrous FeF3 positive electrode material is efficiently synthesized, solving the problem of low theoretical capacity of the existing lithium-ion battery positive electrode material, and achieving electrochemical properties with high energy density and long cycle life.
Patent Information
- Application Number
- CN202311155616.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
The existing lithium-ion battery cathode materials have only involved a single electron reaction and have low theoretical capacity, which cannot meet the needs of high energy density and long cycle life.
The method of direct reaction of F2 and iron precursor is adopted to conduct gas-solid reaction under an inert environment to efficiently synthesize anhydrous FeF3 positive electrode material.
The efficient synthesis of anhydrous high-purity FeF3 material at lower temperatures is achieved, which improves the preparation efficiency. The obtained FeF3 positive electrode material has excellent electrochemical performance, good capacity and circulation performance, low price and non-toxicity.
Smart Images

Figure CN119569130A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a preparation method and application of a lithium-free positive electrode FeF3 active material. Background Art
[0002] Lithium-ion batteries are important energy storage devices that are currently widely used in electric vehicles, mobile devices and other fields. Among them, the positive electrode material, as an important component of lithium-ion batteries, has an important impact on the performance and cycle life of the battery. Currently, the commonly used lithium-ion battery positive electrode materials are mainly based on lithium-containing oxides, such as LiCoO2, LiFePO4, LiNi x Mn y Co z O2, etc. However, with the continuous development of the economy and society, people's demand for high-energy-density cathode materials is increasing. Commercial cathode materials cannot meet the requirements because the intercalation reaction only involves a single electron reaction and the theoretical capacity is low. Therefore, it is urgent to develop a new generation of lithium-ion battery cathode materials with higher energy density and long cycle life. In the past few years, multi-electron materials have aroused great interest because they can realize the transfer of multiple electrons through conversion reactions. Among them, metal fluoride FeF3 has attracted widespread attention from researchers due to its high theoretical capacity, large reserves of elements in the earth's crust, and low cost. As a new type of lithium-ion battery cathode material, FeF3 can be combined with Li + The deintercalation reaction can also utilize all the oxidation states of Fe to react with Li + A chemical conversion reaction occurs, and because there is a transfer of three electrons in the reaction, its theoretical specific capacity is relatively high. In the voltage range of 2.0-4.5V, the theoretical specific capacity is 237mAh / g, and in the voltage range of 1.0-4.5V, the theoretical specific capacity is 712mAh / g. It has broad prospects for application in positive electrode materials.
[0003] The main methods for preparing FeF3 include liquid phase method, template method, gas phase method, etc. 1. Liquid phase method: First, the reactants are prepared into a solution in a certain proportion, and FeF3 hydrate is obtained through chemical reaction, and then treated at high temperature to remove the crystal water. This method is easy to operate and has low equipment requirements. It is widely used in laboratories and industries, but the prepared particle size is generally micron-level, which is not conducive to electrochemical reactions. 2. Template method: First, the precursor is deposited on the template, and then a specific solvent is selected to remove the template. By selecting different templates, the morphology and size of the material can be adjusted. The special nanostructure obtained is conducive to the transmission of ions and electrons, and can also be in-situ composited with conductive polymers on the surface, reducing the charge transfer impedance of FeF3, thereby improving the rate performance. 3. Gas phase method: Using the strong oxidizing property of fluorine-containing gases, such as HF, NF3, etc., to react with iron sources such as Fe2O3 and FeCl3, the FeF3 particles obtained are larger in size and the material is loose and porous.
[0004] The common synthesis route is to use HF or NH4F to provide a fluorine source for precursors such as FeCl3. This method usually forms a hexagonal tungsten bronze structure of FeF3 hydrate (HTB-FeF3). It is difficult to obtain anhydrous FeF3, so a secondary high-temperature treatment in an inert atmosphere is required to achieve complete dehydration of the compound. The use of these traditional methods to synthesize anhydrous FeF3 has a complex preparation process and high cost, which is not conducive to its practical application in the industrial field. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a lithium-free positive electrode FeF3 active material. The method adopts F2 to directly react with an iron precursor, can efficiently synthesize anhydrous FeF3 positive electrode materials, the process is simple, and the obtained FeF3 positive electrode material has excellent electrochemical properties, good capacity and cycle performance.
[0006] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a lithium-free positive electrode FeF3 active material, the preparation method comprising:
[0007] The iron-based precursor is added into the reactor and heated under an inert environment to remove water vapor;
[0008] F2 is introduced into the reactor at a preset flow rate, and at a set temperature, F2 reacts with the iron-based precursor in a gas-solid manner;
[0009] The reaction product is cooled to obtain a lithium-free positive electrode FeF3 active material.
[0010] Preferably, the heating temperature under the inert environment is 90°C-130°C, and the heating time is 0.5-2h; the inert gas is nitrogen;
[0011] Preferably, the iron-based precursor comprises: any one or a combination of iron powder, Fe2O3, FeSi, FeSi2, FeCl3 and FeS2, with an average particle size of 10-300nm; the purity of the iron-based precursor is 98.0-99.9%.
[0012] Preferably, the gas-solid reaction between F2 and the iron-based precursor is specifically as follows:
[0013] The F2 reacts with the iron-based precursor in a gas-solid manner to generate anhydrous FeF3, or to generate anhydrous FeF3 and a gaseous compound.
[0014] Preferably, the preset flow rate is 5-20 mL / min, the set temperature is 200-600° C., and the reaction time of the gas-solid reaction is 4-15 hours.
[0015] In a second aspect, an embodiment of the present invention provides a lithium-free positive electrode FeF3 active material prepared by the preparation method described in the first aspect above.
[0016] In a third aspect, an embodiment of the present invention provides a positive electrode, comprising a lithium-free positive electrode FeF3 active material prepared by the preparation method described in the first aspect above.
[0017] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode described in the third aspect.
[0018] The method for preparing the lithium-free positive electrode FeF3 active material provided in the embodiment of the present invention uses an iron precursor and F2 to directly perform a gas-solid reaction at a set temperature, and can efficiently synthesize anhydrous high-purity FeF3 materials at a relatively low temperature, thereby improving the preparation efficiency. The FeF3 positive electrode active material synthesized by the present invention is inexpensive and non-toxic, has a high discharge voltage platform and theoretical capacity, and is prepared by this method, which effectively improves the energy density and enhances the stability of the material. The application of the lithium-free positive electrode active material FeF3 helps to reduce dependence on lithium resources and solve the problem of limited resources of positive electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A schematic diagram of a method for preparing a lithium-free positive electrode FeF3 active material provided in an embodiment of the present invention;
[0020] Figure 2 A diagram of a reaction device for fluorination for implementing the preparation method of the present invention provided in an embodiment of the present invention;
[0021] Figure 3 The charge and discharge curve of the FeF3 active material prepared in Example 1-2 of the present invention;
[0022] Figure 4The rate performance diagram of the FeF3 active material prepared in Examples 1-3 of the present invention;
[0023] Figure 5 This is a cycle performance curve diagram of the FeF3 active material prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0025] The present invention provides a method for preparing a lithium-free positive electrode FeF3 active material, the main steps of which are as follows: Figure 1 As shown, the method can be executed as follows Figure 2 Of course, it can be understood that the schematic diagram of the reaction device is only an illustrative illustration that can be implemented. The device structure that can implement the preparation method of the present invention is not limited to this one. Those skilled in the art can select the reaction device according to actual production or experimental needs.
[0026] The main steps of the preparation method of the present invention include:
[0027] Step 110, adding an iron-based precursor into a reactor and heating it under an inert environment to remove moisture;
[0028] The iron-based precursor comprises: any one or a combination of iron powder, Fe2O3, FeSi, FeSi2, FeCl3 and FeS2, with an average particle size of 10-300nm; the purity of the iron-based precursor is 98.0-99.9%.
[0029] The heating temperature under an inert environment is 90° C.-130° C., and the heating time is 0.5-2 h; the inert gas is preferably nitrogen.
[0030] Step 120, introducing F2 into the reactor at a preset flow rate, and at a set temperature, F2 reacts with the iron-based precursor in a gas-solid reaction;
[0031] Specifically, F2 reacts with the iron-based precursor to generate anhydrous FeF3, or to generate anhydrous FeF3 and a gaseous compound. The preset flow rate is 5-20 mL / min, the set temperature is 200-600° C., and the reaction time of the gas-solid reaction is 4-15 hours.
[0032] Step 130, cooling the reaction product to obtain a lithium-free positive electrode FeF3 active material.
[0033] The method for preparing the lithium-free positive electrode FeF3 active material provided in the embodiment of the present invention uses an iron precursor and F2 to directly perform a gas-solid reaction at a set temperature, and can efficiently synthesize anhydrous high-purity FeF3 materials at a lower temperature, thereby improving the preparation efficiency. The lithium-free positive electrode FeF3 active material prepared by the above preparation method can be used in lithium-ion batteries. By using the lithium-free positive electrode material FeF3, it helps to reduce dependence on lithium resources and solve the problem of limited positive electrode material resources for lithium-ion batteries.
[0034] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only partial embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention. In addition, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing a lithium-free positive electrode FeF3 active material, comprising the following steps:
[0037] Ultrafine iron powder with a purity of 99.0% and an average particle size of 200 nm was added to a nickel reactor. Before the reaction, the iron powder was heated in a nitrogen atmosphere at 130°C for 1 hour to remove trace moisture, and then F2 was introduced into the reactor, the gas flow rate was controlled to be 10 mL / min, the temperature was 340°C, the reaction time was 10 hours, and the reaction equation was as follows: 2Fe+3F2→2FeF3. The product was collected after cooling.
[0038] Example 2
[0039] This embodiment provides a method for preparing a lithium-free positive electrode FeF3 active material, comprising the following steps:
[0040] Fe2O3 with a purity of 98.5% and an average particle size of 20 nm was added to a nickel reactor. Before the reaction, Fe2O3 was heated at 100°C in a nitrogen atmosphere for 1.5 h to remove trace moisture. Then F2 was introduced into the reactor, and the gas flow rate was controlled to be 20 mL / min, the temperature was 280°C, and the reaction time was 12 h. The reaction equation is as follows: After cooling, the product was collected.
[0041] Example 3
[0042] This embodiment provides a method for preparing a lithium-free positive electrode FeF3 active material, comprising the following steps:
[0043] FeSi with a purity of 99.5% and an average particle size of 49 nm was added to a nickel reactor. Before the reaction, FeSi was heated at 90°C in a nitrogen atmosphere for 2 h to remove trace moisture. Then F2 was introduced into the reactor, and the gas flow rate was controlled to be 12 mL / min, the temperature was 300°C, and the reaction time was 15 h. The reaction equation is as follows: After cooling, the product was collected.
[0044] Example 4
[0045] This embodiment provides a method for preparing a lithium-free positive electrode FeF3 active material, comprising the following steps:
[0046] FeSi2 with a purity of 99.9% and an average particle size of 100 nm was added to a nickel reactor. Before the reaction, FeSi2 was heated at 100°C in a nitrogen atmosphere for 2 h to remove trace moisture. Then F2 was introduced into the reactor, and the gas flow rate was controlled to be 8 mL / min, the temperature was 450°C, and the reaction time was 16 h. The reaction equation is as follows: After cooling, the product was collected.
[0047] Example 5
[0048] This embodiment provides a method for preparing a lithium-free positive electrode FeF3 active material, comprising the following steps:
[0049] FeCl3 with a purity of 99.0% and an average particle size of 150 nm was added to a nickel reactor. Before the reaction, FeCl3 was heated at 110°C in a nitrogen atmosphere for 1 hour to remove trace moisture. Then F2 was introduced into the reactor, and the gas flow rate was controlled to be 5 mL / min, the temperature was 480°C, and the reaction time was 10 hours. The reaction equation was as follows: 2FeCl3+3F2→2FeF3+3Cl2↑. The product was collected after cooling.
[0050] Example 6
[0051] This embodiment provides a method for preparing a lithium-free positive electrode FeF3 active material, comprising the following steps:
[0052] FeS2 with a purity of 98.5% and an average particle size of 70 nm was added to a nickel reactor. Before the reaction, FeS2 was heated at 90°C in a nitrogen atmosphere for 2 h to remove trace moisture. Then F2 was introduced into the reactor, and the gas flow rate was controlled to be 15 mL / min, the temperature was 600°C, and the reaction time was 8 h. The reaction equation is as follows: After cooling, the product was collected.
[0053] The electrochemical performance of the products prepared in the above examples 1-6 was tested:
[0054] The obtained product, FeF3 active material of lithium-free positive electrode, conductive carbon black super P, and polyvinylidene fluoride (PVDF), were weighed and ground according to a mass ratio of 7:2:1. After grinding evenly, N-methylpyrrolidone (NMP) solution was added and stirred until the viscosity reached the coating requirement. Then, the slurry was evenly applied on aluminum foil using a coating machine. The electrode was dried at 80°C for 2h and vacuum dried at 100°C for 12h. The electrode sheet was cut into discs with a diameter of 12mm. The loading amount of active material on each disc was about 2.5mg / cm 2 The prepared electrode sheet was used as the positive electrode, the lithium sheet as the negative electrode, Celgard 2500 as the separator, and the organic mixture of ethylene carbonate (EC) / dimethyl carbonate (DMC) (v:v=1:1) with a concentration of 1 mol / L LiPF6 as the electrolyte. The CR2032 button cell was assembled in an argon-filled glove box. The battery was left to stand for 10 hours, and the charge and discharge and rate tests (1C=237mAh / g) were performed on a Blue Power Battery Test System (CT2001A) at room temperature, with a voltage range of 2-4.5V.
[0055] The button cells prepared in Example 1 and Example 2 were subjected to the first week charge and discharge test, and the curves are as follows: Figure 2 As shown, the charge specific capacity of Example 1 is 183.6 mAh / g, and the discharge specific capacity is 203.1 mAh / g; the charge specific capacity of Example 2 is 185.2 mAh / g, and the discharge specific capacity is 205.8 mAh / g.
[0056] The button cells prepared in Examples 1-3 were tested for rate performance. Figure 4 This is the rate performance diagram of the FeF3 active material prepared in Examples 1-3 of the present invention. The test rate procedure is to change the discharge rate to 0.2C, 0.5C, 1C, 2C, 5C, and 10C in sequence, and then the discharge rate is restored to 0.2C. Each of the above rates is cycled for five weeks, and it can be seen that its capacity is very excellent at high rates. Under 5C conditions, the discharge specific capacities of Examples 1-3 can reach 145.4, 150.6, and 148.3 mAh / g, respectively. Under 10C conditions, the discharge specific capacities of Examples 1-3 can reach 114.6, 123.2, and 119.8 mAh / g, respectively. When restored to 0.2C rate conditions, the initial capacity retention rates can reach 95.2%, 95.8%, and 94.7%, respectively.
[0057] Figure 5 The cycle performance curve of the FeF3 active material prepared in Examples 1-3 of the present invention at 0.2C is shown. It can be seen that after 100 cycles, the discharge capacity decay is small, and the capacity retention rates of Examples 1-3 can reach 88.1%, 92.0%, and 87.3%, respectively.
[0058] The FeF3 positive electrode active material synthesized by the preparation method of the present invention has a high discharge voltage platform and theoretical capacity. The material obtained by the preparation method is low-priced and non-toxic. Preparation by this method can effectively improve energy density and enhance material stability.
[0059] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-free positive electrode FeF3 active material, characterized in that: The preparation method comprises: The iron-based precursor is added into the reactor and heated under an inert environment to remove water vapor; F2 is introduced into the reactor at a preset flow rate, and at a set temperature, F2 reacts with the iron-based precursor in a gas-solid manner; The reaction product is cooled to obtain a lithium-free positive electrode FeF3 active material.
2. The preparation method according to claim 1, characterized in that: The heating temperature of the heating under the inert environment is 90° C.-130° C., and the heating time is 0.5-2 h; the inert gas is nitrogen.
3. The preparation method according to claim 1, characterized in that: The iron-based precursor comprises: any one or a combination of iron powder, Fe2O3, FeSi, FeSi2, FeCl3 and FeS2, with an average particle size of 10-300nm; the purity of the iron-based precursor is 98.0-99.9%.
4. The preparation method according to claim 3, characterized in that: The gas-solid reaction between F2 and the iron-based precursor is specifically as follows: The F2 reacts with the iron-based precursor to generate anhydrous FeF3, or to generate anhydrous FeF3 and a gaseous compound.
5. The preparation method according to claim 1, characterized in that: The preset flow rate is 5-20 mL / min, the set temperature is 200-600° C., and the reaction time of the gas-solid reaction is 4-15 hours.
6. A lithium-free positive electrode FeF3 active material prepared by the preparation method described in claims 1-5.
7. A positive electrode, characterized in that The positive electrode comprises a lithium-free positive electrode FeF3 active material prepared by the preparation method described in claims 1-5 above.
8. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode as claimed in claim 7.